β-hydroxybutyrate, a ketone body, suppresses tumor growth, stemness, and invasive phenotypes in non-small cell lung cancer - Yunlong Huang; Jiaxuan Ding; Yufeng Zhu; Jin Shi; Rong Liu; Chunmei Wu; Liangfu Han; Mingfeng Zhang (Cancer Biology & Therapy)
Lung cancer is the most common cancer worldwide. The stemness and metastasis of tumor cells present major challenges to effective lung cancer treatment. Beta-hydroxybutyrate (BHB), a ketone body, plays a key role in various cancers. However, whether BHB mediates the progression of non-small cell lung cancer (NSCLC) remains unclear. The effects of BHB on the proliferation, apoptosis, and metastasis of NSCLC cells were assessed using the Cell Counting Kit 8, flow cytometry, western blotting, and Transwell assays. The sphere formation assay was used to evaluate the impact of BHB on NSCLC cell stemness. The underlying molecular mechanism was investigated through knockdown and overexpression of free fatty acid receptor 3 (FFAR3) using shRNAs and expression vectors in two NSCLC cell lines (NCI-H1975 and PC-9). In vivo, xenograft tumor and liver metastasis models were established in nude mice. BHB treatment reduced viability, stemness, and migratory and invasive abilities of NSCLC cells. BHB also induced apoptosis and increased cleaved caspase-3 levels in these cells. Moreover, BHB suppressed tumor growth and metastasis, and reduced cell stemness in NSCLC tissues in vivo. Mechanistically, FFAR3 knockdown abolished, while FFAR3 overexpression enhanced, the tumor-suppressive effects of BHB, identifying FFAR3 as a key mediator. These data shed light on the role of BHB in NSCLC development and its underlying molecular mechanisms, suggesting a promising treatment strategy for patients with NSCLC.